2022
DOI: 10.1007/s00223-022-00953-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Activity Profiles in Older Adults and Lower Limb Bone Parameters: Observations from the Hertfordshire Cohort Study

Abstract: As muscle strength and function decline with age the optimal high-impact physical activity (PA) required for bone remodelling is rarely achievable in older adults. This study aimed to explore the activity profiles of community-dwelling older men and women and to assess the relationship between individual PA profiles and lower limb bone parameters. Participants from the Hertfordshire Cohort Study wore triaxial accelerometers for 7 days and counts of low (0.5–1.0 g), medium (1.0–1.5 g), and high (> 1.5 g) ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[ 37 ] A third cohort study reported increased cortical area and total area at the tibial shaft with high‐impact PA in women and men with a mean age of 81 years, while there were no changes in the bone structure of the distal tibia. [ 35 ] The discrepancy between the results of these studies may be due to differences in study design, sample size, and responses of the tibia site that was measured, which depends on the type of activity. The tibial shaft contains almost exclusively cortical bone and a thick cortex, while the distal tibia contains mainly trabecular bone and a thin cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] A third cohort study reported increased cortical area and total area at the tibial shaft with high‐impact PA in women and men with a mean age of 81 years, while there were no changes in the bone structure of the distal tibia. [ 35 ] The discrepancy between the results of these studies may be due to differences in study design, sample size, and responses of the tibia site that was measured, which depends on the type of activity. The tibial shaft contains almost exclusively cortical bone and a thick cortex, while the distal tibia contains mainly trabecular bone and a thin cortex.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] In studies where pQCT images were obtained of both the tibial shaft and the distal tibia, the results were ambiguous. [ 35 , 36 , 37 ] From a cross‐sectional study that compared twins who were discordant for leisure time PA during the last 30 years, active twins had larger cortical CSA, thicker cortices, and higher trabecular vBMD at the tibial shaft than their inactive co‐twin. [ 36 ] Another cross‐sectional study reported increased cortical thickness and higher total BMC at the tibial shaft with moderate to vigorous activity in older adults.…”
Section: Discussionmentioning
confidence: 99%